Surface restoration of corrosion pits in 316L stainless steel through modified metal injection molding - Romanes, Maia (2002)
Pitting corrosion represents a critical failure mechanism in stainless steel structures, as it may lead to structural failure even with negligible loss in metal weight. In 316L stainless steels, pitting creates highly convoluted single-mouthed cavities whose walls consist of convex and concave surfaces of high surface energy. These cavities eventually penetrate through the thickness of the metal causing failures in container applications. This study investigated the use of very fine metal powder as filler material to repair stainless steel surfaces that have been attacked by pitting corrosion. Pits were infiltrated under pressure with a molten feedstock through a modified Metal Injection Molding (MIM) process.